Effect of a Bacillus velezensis and Lysinibacillus fusiformis-based biofertilizer on phosphorus acquisition and grain yield of soybean - Vitorino, Luciana Cristina; da Silva, Elias José; Oliveira, Marilene Silva; Silva, Isabella de Oliveira; Santos, Lorraine da Silva; Mendonça, Maria Andréia Corrêa; Oliveira, Thais Cristina Sousa; Bessa, Layara Alexandre (Frontiers in Plant Science, 2024)
Phosphate-solubilizing bacteria that act through acidification (organic acid synthesis) or mineralization (production of enzymes such as phytase and phosphatases) have been used as a biotechnological alternative to improve plant access to phosphorus (P) retained in organic and inorganic forms in agricultural soils. This study tested the hypothesis that applying a biofertilizer composed of a recognized phosphate-solubilizing bacterium (Bacillus velezensis -strain BVPS01) and an underexplored plant growth-promoting bacterium (Lysinibacillus fusiformis -strain BVPS02) improves growth and grain yield of Glycine max plants. Initial in vitro tests were conducted to assess the functional traits of these bacteria and a mix of the strains BVPS01 and BVPS02 was produced and tested under field conditions to assess its agronomic efficiency. The results confirmed the hypothesis that the tested biofertilizer improves the agronomic performance of Glycine max L. plants in the field. The B. velezensis strain (BVPS01) exhibited a functional trait for producing phosphatase enzymes by expressing the phoC and phoD genes, whereas L. fusiformis strain (BVPS02) solubilized phosphates by organic acid-and phytase-related pathways, synthesized indole-3-acetic acid, and increased the mitotic index in the root meristem of G. max plants. These strains showed biological compatibility, and the formulated product based on these rhizobacteria increased root development and the number of nodules and flowers, positively affecting 1000-grain weight, grain yield, and grain P content. Thus, the tested biofertilizer showed potential to improve root growth and increase grain yield and quality of soybean crops, making it a sustainable and lowcost strategy.